2017
DOI: 10.1177/0271121417740637
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Parents to Implement Functional Communication Training for Young Children With Developmental Delays

Abstract: Approximately one in four young children with developmental delays (DD) engage in challenging behavior, which can affect the child's immediate social and educational outcomes, as well as long-term employment outcomes (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…The results of this study demonstrate the link between educator and child behavior. Increases in paraprofessional FCT fidelity were associated with decreases in child challenging behavior, which is consistent with previous research on natural change agent training in FCT (Gerow et al, 2018). Changes in child behavior began to emerge before the paraprofessionals reached 100% fidelity.…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study demonstrate the link between educator and child behavior. Increases in paraprofessional FCT fidelity were associated with decreases in child challenging behavior, which is consistent with previous research on natural change agent training in FCT (Gerow et al, 2018). Changes in child behavior began to emerge before the paraprofessionals reached 100% fidelity.…”
Section: Discussionsupporting
confidence: 90%
“…This initial study has implications for the training and dissemination of applied behavior analytic technologies to families in need. Gerow et al (2018b) indicated that current studies demonstrating the success of parent-implemented interventions typically rely on direct parent training by highly trained professionals, such as BCBAs. They concluded that there is a lack of studies demonstrating that parents can be successfully trained by the existing professionals with whom they typically interact.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, researchers have relied on the use of highly trained professional supports (BCBA, or other specifically trained individuals) in the delivery of services via telehealth (Gerow et al, 2018b;Suess et al, 2016;Wacker et al, 2013aWacker et al, , 2013b, as opposed to training existing service providers who typically interact with the parents (e.g., special educators, community-based behavioral therapists, behavioral consultants). Gerow et al (2018a) noted that there is a lack of research examining if parents can be trained to implement assessment and intervention procedures, by the existing service providers that are typically accessible to them.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…VR-BST was effective in teaching individuals to implement FCT for problem behavior maintained by attention (10 participants) and by escape (five participants) to mastery criterion Contrary to other published results, seven participants' performance met the mastery criterion following instructions and modeling (cf. Gerow et al, 2018;Suess et al, 2014). That is, performance feedback was not necessary.…”
Section: Discussionmentioning
confidence: 99%